2008
DOI: 10.1007/s11062-009-9046-7
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic Effect of Dexamethasone: Weakening upon the Action of Antidepressants

Abstract: Dose-dependent neurotoxic effects (decrease in the amplitude of field potentials generated by neurons of the СА1 area, dentate gyrus, and dorsal striatum, but not by neurons of layers ІІ and ІІІ of the parietal cortex, recorded in slices of the rat brain) were observed 24 h after i.p. injection оf dexamethasone in doses of 7 and 20 mg/kg. Dexamethasone-induced decreases in the reactivity of glutamatergic synapses in the studied cerebral structures were weakened by a noncompetitive blocker of NMDA receptors, ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…In accordance with previous findings [ 30 32 ], the present study showed that dexamethasone injection for 7 days slightly reduced brain weight and survival rate compared to control group. Also, histopathological examination of the cerebral cortex using H&E and Nissl stains showed marked degeneration in the cortical neurons and disruption of its integrity.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In accordance with previous findings [ 30 32 ], the present study showed that dexamethasone injection for 7 days slightly reduced brain weight and survival rate compared to control group. Also, histopathological examination of the cerebral cortex using H&E and Nissl stains showed marked degeneration in the cortical neurons and disruption of its integrity.…”
Section: Discussionsupporting
confidence: 93%
“…Dexamethasone neurotoxicity has been reported in several previous experimental and clinical studies [ 30 32 ]. Intraperitoneal injection of either 7 or 20 mg/kg dexamethasone caused neurotoxicity in the cerebral cortex after 24 hours by increasing the activity of N-methyl D-aspartate (NMDA) receptors and suppression of neurotrophins [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique was described in detail earlier [14]. Briefly, the rats were decapitated under ketamine anesthesia (50 mg/kg, i.p.).…”
Section: Methodsmentioning
confidence: 99%